2020
DOI: 10.1002/tox.23004
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of serum‐dependent impacts on intracellular accumulation and genomic response of per‐ and polyfluoroalkyl substances in a placental trophoblast model

Abstract: Per‐ and polyfluoroalkyl substances (PFAS), a class of environmental contaminants, have been detected in human placenta and cord blood. The mechanisms driving PFAS‐induced effects on the placenta and adverse pregnancy outcomes are not well understood. This study investigated the impact of perfluorooctanesulfonic acid (PFOS), perfluorooctanoic acid (PFOA), and a replacement PFAS known as hexafluoropropylene oxide dimer acid (HFPO‐DA, tradename GenX) on placental trophoblasts in vitro. Several key factors were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…These concentration ranges overlap with concentrations of PFAS reported in serum of people in highly contaminated communities (PFOA: 17.6 μg/ml; Steenland et al, 2009 ). PFAS concentrations reported in the serum of pregnant women (PFOS in the 95th percentile of exposure = 0.018 μg/ml; Bommarito et al, 2021 ) and concentrations measured in human placental samples (maximum PFHxA = 0.006 μg/g; Bangma et al, 2020b ) are within two to four orders of magnitude of the concentrations tested in the present work. Notably, Bommarito et al (2021) reported maternal PFOS exposure was associated with higher odds of late-onset preeclampsia (OR = 1.60, 95% CI: 1.06, 2.43).…”
Section: Discussionsupporting
confidence: 62%
“…These concentration ranges overlap with concentrations of PFAS reported in serum of people in highly contaminated communities (PFOA: 17.6 μg/ml; Steenland et al, 2009 ). PFAS concentrations reported in the serum of pregnant women (PFOS in the 95th percentile of exposure = 0.018 μg/ml; Bommarito et al, 2021 ) and concentrations measured in human placental samples (maximum PFHxA = 0.006 μg/g; Bangma et al, 2020b ) are within two to four orders of magnitude of the concentrations tested in the present work. Notably, Bommarito et al (2021) reported maternal PFOS exposure was associated with higher odds of late-onset preeclampsia (OR = 1.60, 95% CI: 1.06, 2.43).…”
Section: Discussionsupporting
confidence: 62%
“…Numerous studies have illustrated that exposure to PFOA adversely affects the different organ tissues or cells, such as inducing splenic atrophy, 9 promoting diabetic renal injury, 10 affecting immune organs function, 11 inducing developmental cardiotoxicity, 12 and regulating inflammatory response 13 14 impairing sperm motility, 15 disrupting the hormonal pathways, 16 and causing placental abnormalities, 4,17 as well as its adverse effects on offspring growth and development 18–21 . Moreover, a study of IVF data in humans showed that the maternal plasma PFOA concentration was inversely correlated with the number of obtained oocytes, mature oocytes, 2PN fertilized oocytes, and high‐quality embryos, suggesting that PFOA hurts the female reproductive system 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, studying the effects of short‐chain PFAS on placental cells is of considerable significance while studying human health effects. A study using HT cells (another placental trophoblast model) found that serum‐free media (SFM) contained no detectable PFAS; however, fetal bovine serum‐supplemented media (SSM) was contaminated with legacy PFAS that have the potential to alter the outcomes experiments carried out using fetal bovine serum (Bangma et al, 2020). Albeit the PFAS from the supplemented media were not found in the JEG‐3 cells in this study, however, it highlights another consideration when selecting the culture conditions for short‐chain PFAS studies.…”
Section: Advantages and Limitations Of In Vitro Methodsmentioning
confidence: 99%